Analisis Model Antrian Single Channel Single Phase Pada Pelayanan Publik SPBU Simpang Mangga - Hasibuan, Mhd. Sahdani Rafli; Reza, Aldito Fiter Vanesa; Irawan, M Fahri; Yudha, Hasan Wira; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
This research analyzes the single channel singlephase queuing model for public services at the Simpang Mangga Public Fuel Filling Station (SPBU). Public services play an important role in meeting the diverse needs of society, with efficiency and effectiveness becoming a major concern due to increasing public demands for quality services. Queuing models serve as a valuable approach to analyzing and optimizing service systems by understanding customer arrival patterns, service capacity, and service duration. This research uses quantitative methods with a descriptive-analytical approach, collecting data through direct observation for one hour to assess customer arrival times, service times and waiting times. The research results show that the average customer arrival interval is 5 minutes, with gas stations capable of serving 30 customers per hour. The level of service intensity (p) was recorded at 0.17, indicating that service facilities were only filled with customer service as much as 17%. The average number of customers in the system (L) is 0.2, and the average number of customers waiting (Lq) is 0.03. The average time spent by customers in the system (W) is 0.04 minutes, while the average waiting time in queue (Wq) is 0.01 minutes. These findings highlight the effectiveness of single-phase single-channel models in improving service efficiency and customer satisfaction. Recommendations include increasing service capacity and optimizing the queuing system to reduce waiting times and improve overall service quality.